ANALISIS KUALITAS PELAYANAN PUBLIK DALAM MENINGKATKAN KINERJA PEGAWAI DI DINAS KESEHATAN KABUPATEN KAUR - Tarigan, Debhora (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
The aim of this research is to analyze the quality of service and activities of Kaur Regional Health Service employees. Service quality is studied in seven dimensions. Attitude, approach, performance, energy, character, responsibility and facilities). Meanwhile, employee performance will be seen from 5 (five) dimensions, namely: suitability of service, timeliness, initiative, ability and communication. The main method of data collection is interviews. Interviews were conducted with 5 informants. Data analysis was carried out in a qualitative descriptive manner, namely by providing sentence or narrative explanations. After data analysis, it was discovered that of the 7 (seven) dimensions of service quality studied, not all of them were good and met expectations, namely action (action), accountability (responsibility), and equipment (facilities), so the quality of service was still not good. The results of research on employee performance show that not all of the 5 (five) dimensions studied are good, these dimensions are related to punctuality, so employee performance is not yet completely good. This is because the quality of service is still not good. For this reason, the quality of service in the future still needs to be improved to increase worker performance.